Relationship Between Tracheal Suctioning Catheter Motion and Secretion Amount Based on Viscosity. (October 2020) - Colley, Noriyo; Komizunai, Shunsuke; Konno, Atsushi; Kanai, Satoshi; Ninomiya, Shinji
Background: To provide safe tracheal suctioning, the American Association of Respiratory Care guideline discusses the length of suctioning catheter, but the most effective tracheal suctioning catheter technique is still unknown. Objective: The aim of this study is to compare the amount of simulated secretion produced by five different handlings of a catheter at two different viscosities and in two different models to discover the most effective suctioning maneuver in the various mucus conditions. Design: In vitro experimental design. Methods: The amount of secretion aspirated by our researcher's manipulation of a suctioning catheter was measured. The tip of the catheter was recorded using a high-speed video camera to visualize the secretion motion. Results: The most effective suctioning technique differed depending on the viscosity of the secretion. There were no significant differences between five suctioning methods applied to high-viscosity phlegm in a tracheal membrane model, but the flexion technique was the most efficient for low-viscosity secretion. Conclusions: Our results imply that the flexion technique was reasonably safe and the most effective of these five methods for low-viscosity secretion.